2003
DOI: 10.1097/00001888-200312000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Undergraduate Medical Curriculum on Students??? Self-Directed Learning

Abstract: This study found no evidence that students' self-reported SDL is positively influenced by the current undergraduate medical curriculum at the University of Toronto Faculty of Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 9 publications
0
48
2
2
Order By: Relevance
“…Similarly, Harvey and colleagues, using the SDLRS instrument developed by Guglielmino, found no differences in the readiness for self-directed learning among first-, second-, third-, and fourth-year medical students. 25 However, unlike our study, Harvey and colleagues did not follow the same cohort of students as they progressed through the curriculum. Walker and colleagues investigated the impact of a 16-week problem-based learning curriculum on pharmacy students' readiness for self-directed learning and found an 11-point decrease in students' mean SDLRS scores from baseline.…”
Section: 23mentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly, Harvey and colleagues, using the SDLRS instrument developed by Guglielmino, found no differences in the readiness for self-directed learning among first-, second-, third-, and fourth-year medical students. 25 However, unlike our study, Harvey and colleagues did not follow the same cohort of students as they progressed through the curriculum. Walker and colleagues investigated the impact of a 16-week problem-based learning curriculum on pharmacy students' readiness for self-directed learning and found an 11-point decrease in students' mean SDLRS scores from baseline.…”
Section: 23mentioning
confidence: 70%
“…Harvey and colleagues suspected a ceiling effect when examining the readiness of medical students for self-directed learning. 25 Finally, this study investigated pharmacy students' readiness for self-directed learning and not actual participation in self-directed learning activities. To maintain one's competency, one must not only be ready to engage in selfdirected learning but must actually implement it.…”
Section: 23mentioning
confidence: 99%
“…This research found that those with master's and doctorate degrees had higher SDLRS scores. 17 Even though only a small percentage of students failed to answer the survey instruments completely, this may have impacted our results. Further, when associate's/bachelor's and master's/doctorate degree groups were combined to increase group size, statistical significance was lost, highlighting this potential limitation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous research of medical students using an alternative SDLRS failed to show a difference in SDLRS scores between firstthrough fourth-year students. 17 Further research in our population is warranted to evaluate changes in SDLRS score as this cohort moves through the curriculum.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study with nursing students in a PBL curriculum found no significant difference in overall SDLR level after 1 year of education (Williams, 2001), although qualitative results from the same study revealed students described the development of many of the characteristics associated with SDL. Another study with medical students reported no significant change in SDLR scores (Harvey, Rothman, & Frecker, 2003), whereas Walker and Lofton (2003) reported a decrease in SDLR scores of PBL students in the first 16 weeks of their pharmacy education.…”
Section: Problem-based Learning and Self-directed Learningmentioning
confidence: 97%